The title to be addressed in the system of kinship of Laotian ( Lao – Lum ) - CHANHTHAHONG , Khamxay; SYSOUPHANH, Sangkhom (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The objectives of this investigation were to collect all the details of the titles to be named in Lao Lum ethnic group kinship. to clarify Lao Lum kinship titles. The kinship titles named in the Lao Lum ethnic group can be divided into two types, female and male’s titles. The female’s titles consisted of great grandmother, grandmother, aunts, and sisters, while the male’s titles were great grandfather, grandfather, uncles, and brothers. In addition, there was an unidentified sex group including children, grandchildren, great grandchildren and others. The titles to be addressed in Lao Lum kinship was dependent on personal statuses, these included elderly, older and younger. The title was used to show honor and respect within the kinship and also others in the society. Furthermore, it helped to clarify personal title.